Exploring the Influence of Azo Dye Congo Red on Acinetobacter baumannii YNWH 226 Growth: A Secondary Modeling Study (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2023)
One of the challenges that face the textile industry is the release of effluents that are not wanted, most notably colors that do not degrade. This is one of the issues that plagues the industry. This is a concern since it affects the environment. Bioremediation using dye-degrading bacterium is appealing as bacterial metabolism converts hazardous dye to harmless carbon dioxide and water as byproducts. In this study, various secondary growth models such as Luong, Yano, Teissier-Edward, Aiba, Haldane, Monod, Han, and Levenspiel were employed. Following thorough statistical analyses such as root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), bias factor (BF), and accuracy factor (AF), the Luong model emerged as the most optimal choice. the half-saturation constant for maximal growth, maximal growth rate and maximal concentration of substrate tolerated and curve parameter that defines the steepness of the growth rate decline from the maximum rate symbolized by Ks, max and Sm, and n were 8.023 mg/L (95% C.I., -153.852 to 169.898), 0.437 per d (95% C.I., -0.121 to 0.995), 551.629 mg/L (95% C.I., 378.823 to 724.435) and 3.907 (95% C.I., -8.808 to 16.621), respectively.  These novel constants discovered during the modeling process could serve as valuable inputs for subsequent modeling pursuits.
Keywords: Biodegradation; Congo red; Inhibition kinetics; Azo dye; Acinetobacter baumannii